Caracterização e adequação dos resíduos da construção civil produzidos no município de Santa Maria-RS para aplicação em pavimentação - Delongui, Lucas (2012)
The civil construction industry is characterized for being the sector that suffers the most influence with the economy growth. Government policies to encourage housing instigate the sector to produce wildly, using outdated construction techniques and employing unskilled labor, in an attempt to reduce costs and shorten timeline. The result of this impetus is the great generation of waste which, when untreated, are thrown into nature, causing irreparable environmental impacts. However, the recycling and production processes of recycled aggregates from construction waste (C&D waste) are consolidated in Brazil, but the same cannot be said of the use of these aggregates. Therefore, this study aims to characterize the recycled aggregates produced in Santa Maria to promote their use in paving. For this, the research was divided into three stages which contemplated the current situation of the C&D waste in the city: treatment and processing, characterization of recycled aggregates and possible implementation. The first phase consisted of the analysis of the waste management system employed in the city, which exposes an assessment of the management system since the implementation of the C&D waste treatment area, as well as reports examples and consequences of irregular disposal. The second stage involved the laboratory analysis, where the aggregates were divided according to the commercial size of gravel in the region and dosed properly to fit standards within the limits shown in the DNIT for granular material. From this, the aggregates were characterized and tested to see if they meet the criteria adopted by the NBR 15116, which specifies limits for use of this material in pavement. The third part consisted of the analysis of economic viability. This analysis was estimated by scaling up floors consisting of crushed stone and the other by recycled aggregate that presented the same responses to these efforts, and then the costs for obtaining and execution of the respective layers executed with these materials were compared. The results demonstrated that the aggregates meet the regulatory specifications for even high traffic volumes. In general, recycled aggregates, achieve better results when subjected to intermediate compaction energy, behaving similarly to gravel.